2000
DOI: 10.1002/1099-0488(20001015)38:20<2644::aid-polb40>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and disaggregation of Aeromonas gum in an aqueous solution under different conditions

Abstract: The aggregation and disaggregation of Aeromonas (A) gum, an acidic heteropolysaccharide, were investigated by viscometry, a fluorescent probe, and gel permeation chromatography combined with laser light scattering techniques in aqueous solutions containing desired NaCl at different temperatures. The A gum had a strong tendency of aggregation and high viscosity in the aqueous solutions. The weight‐average molecular weight, z‐average radius of gyration, weight‐average molar number (wag), and apparent aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…It is likely that, to a large extend 3,6‐O‐CM‐chitin exists in aqueous solution as aggregates and the increasing temperature leads to disruption of the aggregates by destruction of the aggregating interactions. The dissociation process of the aggregates can be ascribed as follows, taking reference to the literature 5. When the system obtained a certain energy above 60°C, the aggregates with relatively low cohesive energy were first dissociated, the aggregates with middle cohesive energy were then dissociated at 80 to 90°C, and a small part of aggregates with high cohesive energy were difficult to be dissociated by heating.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is likely that, to a large extend 3,6‐O‐CM‐chitin exists in aqueous solution as aggregates and the increasing temperature leads to disruption of the aggregates by destruction of the aggregating interactions. The dissociation process of the aggregates can be ascribed as follows, taking reference to the literature 5. When the system obtained a certain energy above 60°C, the aggregates with relatively low cohesive energy were first dissociated, the aggregates with middle cohesive energy were then dissociated at 80 to 90°C, and a small part of aggregates with high cohesive energy were difficult to be dissociated by heating.…”
Section: Resultsmentioning
confidence: 99%
“…This result seems to be different from those obtained by Eisenberg and Zhang et al Eisenberg et al1 reported two block polyelectrolyte samples as a function of NaCl concentration, and found that at low salt concentration ( c s < 0.2 M ) aggregation numbers initially increased with c s and then eventually leveled off. Zhang et al5 reported that the aggregation behavior of Aeromonas gum was almost independent of the salt concentration, but reduced dimensions caused by decrease of electrostatic force was likely to have strong effect on [η], thus intrinsic viscosity [η] decreased with salt concentration. To verify the result obtained from viscometry method, 3,6‐O‐CM‐chitin solutions of desired NaCl concentration were injected into the GPC column at 30°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations